The Guidelines for Developing of Ordinary Scout Activities of School Under The MahaSarakham Primary Education Service Area Office 2: The Guidelines for Developing of Ordinary Scout Activities of School Under The MahaSarakham Primary Education Service Area Office 2 - mahad, Kunakorn; Duangchatom, Kritkanok (RATANABUTH JOURNAL, 2023)
The purposes this research were to 1) study the current conditions, desirable condition and need assessment of developing of ordinary scout activities of school under the Maha Sarakham primary education service area office 2. 2) study the guidelines for developing of ordinary scout activities of school under the Maha Sarakham primary education service area office 2. The research was divided into 2 phases: Phase 1 study the current conditions, desirable condition and need assessment of developing of ordinary scout activities of school. The sample group were 309 school administrators and teachers. The research instrument were questionnaires discrimination was 0.32–0.87, reliability of .92. The statistics used for data analysis were mean and deviation standard. Phase 2: study the guidelines for developing of ordinary scout activities of school. The target groups include 9 experts for assess suitability possibility of guideline. The research instrument were interview form and assessment form of guidelines The results of the research were as follows: The current state in overall was high, the desirable state in overall was in the highest level. The need assessment rank from high to low level was 1) activity 2) scouts 3) goals or ideologies 4) administration 5) scout commanders. 2. the guidelines for developing of ordinary scout activities of school, Include was 1) activity 7 guidelines 2) scouts 4 guidelines 3) goals or ideologies 3 guidelines 4) administration 8 guidelines 5) scout commanders 4 guidelines. Summary of guidelines evaluation, feasibility and utility was the highest in overall.